Missing Concept Extraction Using Rough Set Theory - Nur Fatin Nabila Mohd Rafei Heng; Nurlida Basir; Zaizi N.J.M.; Deris M.M. (Springer Science and Business Media Deutschland GmbH, 2024)
Indexed by Scopus